The impact of agri-business skills training in Zimbabwe: an evaluation of the Training for Rural Economic Empowerment (TREE) programme. Issue 3 (3rd July 2018) - Lachaud, Michée A.; Bravo-Ureta, Boris E.; Fiala, Nathan; Gonzalez, Susana P.
ABSTRACT: This study presents an evaluation of the International Labour Organization (ILO) Training for Rural Economic Empowerment (TREE) programme as implemented in Zimbabwe. The programme's goal was to improve the labour market outcomes of young people in rural areas. We apply Propensity Score Matching and Difference-in-Differences methods on a two-period retrospective panel data survey (2011 and 2014) to control for biases stemming from observed and unobserved time-invariant characteristics between TREE beneficiaries and a constructed control group. We find that TREE increased beneficiaries' income by US 787, as well as child and health expenditures by US 236 and US 101, respectively, compared to non-beneficiaries over the 2011–2014 programme implementation period.